2022
DOI: 10.3389/fvets.2022.1011905
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to demonstrate the paracrine effect of equine, adult allogenic mesenchymal stem cells in vitro, with a potential for healing of experimentally-created, equine thoracic wounds in vivo

Abstract: Regenerative biological therapies using mesenchymal stem cells (MSCs) are being studied and used extensively in equine veterinary medicine. One of the important properties of MSCs is the cells' reparative effect, which is brought about by paracrine signaling, which results in the release of biologically active molecules, which in turn, can affect cellular migration and proliferation, thus a huge potential in wound healing. The objective of the current study was to demonstrate the in vitro and in vivo potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Others have shown that equine MSCs may be applied in the treatment of other conditions, including endotoxemia, inflammatory bowel disease, and several respiratory and reproductive disorders (Cequier et al., 2021 ; MacDonald & Barrett, 2020 ). Equine MSCs have also been investigated for the treatment of integumentary disorders and wound healing, though the effects of MSCs on wound healing were previously shown to be more significant in vitro than in vivo (Caruso et al., 2022 ; Cequier et al., 2021 ). MSCs display broad potential in equine species, but their immunomodulating properties may be affected by high passage numbers, indicating that lower passage numbers of the cells may be needed for them to reach their full therapeutic potential (Connard et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown that equine MSCs may be applied in the treatment of other conditions, including endotoxemia, inflammatory bowel disease, and several respiratory and reproductive disorders (Cequier et al., 2021 ; MacDonald & Barrett, 2020 ). Equine MSCs have also been investigated for the treatment of integumentary disorders and wound healing, though the effects of MSCs on wound healing were previously shown to be more significant in vitro than in vivo (Caruso et al., 2022 ; Cequier et al., 2021 ). MSCs display broad potential in equine species, but their immunomodulating properties may be affected by high passage numbers, indicating that lower passage numbers of the cells may be needed for them to reach their full therapeutic potential (Connard et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%